Konsep Negara Dan Pemerintahan Dalam Perspektif Fikih Siyazah Al-Gazzali - Sahri Sahri (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2013)
As one of the most comprehensive Islamic thinkers in the realm ofthought, al-Gazz?l? to be one of the points of references to Islamic thought inthis day, including in this case is about the concept of state and government.This article wants to show the wealth of thought of al-Gazz?l? relates to stateand government. According to al-Gazz?l?, the political power and religion has avery strong interdependence. This case he is expressed in terms of ad-d?n as?s waa?-?ul??n h?ri? (religion as a basis and sultan or the country as a protector). Thus,al-Gazz?l? firmly stated that the construct of the state and the government isdemand of religion (min dar?riyy?t asy-syari) that can not be ignored (l? sabi?la il? tarkih). Furthermore, in this article, showed that al-Gazz?l? considers the Imamateor the government is a successor of the Prophet. Its because of his function that inheren with the religious issues, so the caliph in running his governmentis regarded as a saint (muqaddas). About the source of authority of power, alGazz?l? considers that it is not a God given (theocracy) but by the support ofthe wider community represented by people who are influential (ahl asy-syawka)and followed by other people. Al-Gazz?l? stressed that the rise and fall of a rulerdepends entirely to the presence and absence of support from the community(Muslims). So, in this case, al-Gazz?l? is differ with the mainstream paradigm ofShiite and also does not have a fatalistic paradigm (Jabariyah).